Application of the wet mount method as an early prevention of Enterocytozoan hepatopenaei (EHP) disease that infects vanname shrimp (Litopanaeus vannmaei) - Esrarf, Hanif Nadhifa (Generasi Biologi Indonesia, 2024)
The cultivation of vannamei shrimp faces persistent challenges, particularly due to various disease outbreaks. One emerging and common disease is Enterocytozoon hepatopenaei (EHP). This disease is caused by the microsporidian parasite, which hinders shrimp growth by infecting the hepatopancreas. This study aims to evaluate the application of the wet mount method as an early prevention strategy for EHP infection in whiteleg shrimp. The research employs a laboratory-based experimental approach using the wet mount method to detect spores/microsporidia in the shrimp hepatopancreas, observed under a microscope at 1.000x magnification. Results from this method revealed a 50% prevalence of spores/microsporidia in shrimp hepatopancreas samples from VIP pond section A1 and 90% prevalence in very very important person (VVIP) pond section A2. Thus, the wet mount method is a viable technique for identifying spores/microsporidia in the hepatopancreas of Litopenaeus vannamei, offering an effective early detection approach for EHP infection.